SuperCooperators: altruism, evolution, and why we need each other to succeed (review) - Rolston, Holmes, 1932-2025, author; Joint Publication Board of Zygon, publisher (Colorado State University. Libraries, 2011)
Martin Nowak hopes by mathematical analysis to show that evolution generates Super-cooperators. Personal anecdotes here undermine his fundamental claim that everything and anything that happens in the universe is the consequence of universal logic acting on universal rules. Nowak presents "the bright side of biology," the importance of cooperation in evolution. He thinks the long-term and ongoing results may be open. "Cooperation comes and goes, waxes and wanes. It has to be reborn in endless cycles." Although his account might show the natural history of how cooperation evolved, it is powerless to explain how a universal ethic could be produced or kept in place, as promoted, for example, by Good Samaritans, who share both compassion and their creeds, so that there is no differential genetic benefit.
This is an electronic version of an article published in Zygon®: Journal of Religion and Science.
Keywords: Nowak, Martin; mathematics; mathematical biology; cooperation; evolution; altruism; Good Samaritan; ethics